2011
DOI: 10.1038/nn.2824
|View full text |Cite
|
Sign up to set email alerts
|

Retinal origin of orientation maps in visual cortex

Abstract: The orientation map is a hallmark of primary visual cortex in higher mammals. It is not yet known how orientation maps develop, what function they play in visual processing and why some species lack them. Here we advance the notion that quasi-periodic orientation maps are established by moiré interference of regularly spaced ON and OFF-center retinal ganglion cell mosaics. A key prediction of the theory is that the centers of iso-orientation domains must be arranged in a hexagonal lattice on the cortical surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

15
194
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 151 publications
(219 citation statements)
references
References 52 publications
15
194
0
Order By: Relevance
“…Thus, we reasoned robust map properties predicted by the seeding mechanism might be detectable in the adult. Indeed, previous work has shown that the predicted hexagonal structure of the interference pattern is reflected in the organization of the orientation map (16,18). Here we use the model to derive a peculiar prediction relating orientation and retinotopic maps and confirm that it holds in tree shrew primary visual cortex.…”
supporting
confidence: 74%
See 4 more Smart Citations
“…Thus, we reasoned robust map properties predicted by the seeding mechanism might be detectable in the adult. Indeed, previous work has shown that the predicted hexagonal structure of the interference pattern is reflected in the organization of the orientation map (16,18). Here we use the model to derive a peculiar prediction relating orientation and retinotopic maps and confirm that it holds in tree shrew primary visual cortex.…”
supporting
confidence: 74%
“…We first consider an ideal version of the model, which helps develop an intuition for how the link between the maps come about. Suppose the receptive fields of ON-center and OFF-center retinal ganglion cells (RGCs) of a given class lie at the vertices of a perfect hexagonal grid (16). When two such patterns, having slightly different periodicities and orientations, are superimposed, the result is a periodic interference pattern (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations